Study of coagulation profile in malaria - Dr. Vibha K Patel; Dr. Nirali Kalpesh Shah; Dr. Anjali Deepak Goyal; Dr. Cherry Kalpesh Shah; Dr. Simul Jagdish Patel (Tropical Journal of Pathology and Microbiology, 2020)
Background: Malaria is a major health problem in many parts of India. Several factors have been attributed to increased morbidity and mortality in malaria with altered hematological and coagulation parameters. This study was conducted to compare the coagulation parameters of malaria cases with those of the healthy carriers. Aims and objectives: To evaluate coagulation abnormalities in patients of malaria and to study the difference in coagulation parameters between malaria patients and healthy controls and to determine the level of significance of the difference. Materials and methodology: This prospective comparative study of 300 patients with laboratory diagnosed malaria patients (cases) and 300 healthy individuals (controls) was carried out in the Department of Pathology in a tertiary care, V. S. General Hospital, Ahmedabad. Result: Comparison of platelet count, PT, and aPTT between case groups and control groups was statistically significant (p<0.001). Conclusion: There is a significant difference between the platelet count, PT, and aPTT values of the two groups. This indicates that in patients with malaria, there is an activation of intrinsic and extrinsic pathways of coagulation.